2003
DOI: 10.1046/j.1365-8711.2003.06638.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields in active galactic nuclei and microquasars

Abstract: Observations of active galactic nuclei and microquasars by ASCA, RXTE, Chandra and XMM–Newton indicate the existence of wide X‐ray emission lines of heavy ionized elements in their spectra. The emission can arise in the inner parts of accretion discs where the effects of general relativity must be counted; moreover, such effects can dominate. We describe a procedure to estimate an upper limit of the magnetic fields in the regions where X‐ray photons are emitted. We simulate typical profiles of the iron Kα line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 89 publications
1
41
1
1
Order By: Relevance
“…Even if we consider a supermassive black hole in the center of the quasar M SMBH = 10 9 M , then its Schwarzschild radius is r g = 3× 10 14 cm and assuming that the emission region for the X-ray radiation is located near the black hole r emission < 100 r g = 3 × † Simulations of X-ray line profiles are presented in a number of papers, see, for example, Zakharov & Repin (2002a,b,c,d, 2003a, 2003c) and references therein, in particular Zakharov et al (2003) showed that an information about magnetic filed may be extracted from X-ray line shape analysis; Zakharov & Repin (2003b) discussed signatures of X-ray line shapes for highly inclined accretion disks, Zakharov et al (2004a) calculated shapes of spectral lines for non-flat accretion flows. 10 16 cm, we obtain that r emission < R EC , therefore the point size source approximation can be adopted for the X-ray emitting region.…”
Section: Cosmological Distribution Of Microlensesmentioning
confidence: 99%
“…Even if we consider a supermassive black hole in the center of the quasar M SMBH = 10 9 M , then its Schwarzschild radius is r g = 3× 10 14 cm and assuming that the emission region for the X-ray radiation is located near the black hole r emission < 100 r g = 3 × † Simulations of X-ray line profiles are presented in a number of papers, see, for example, Zakharov & Repin (2002a,b,c,d, 2003a, 2003c) and references therein, in particular Zakharov et al (2003) showed that an information about magnetic filed may be extracted from X-ray line shape analysis; Zakharov & Repin (2003b) discussed signatures of X-ray line shapes for highly inclined accretion disks, Zakharov et al (2004a) calculated shapes of spectral lines for non-flat accretion flows. 10 16 cm, we obtain that r emission < R EC , therefore the point size source approximation can be adopted for the X-ray emitting region.…”
Section: Cosmological Distribution Of Microlensesmentioning
confidence: 99%
“…A detailed discussion of the magnetic field influence on spectral line shapes for flat accretion flows was given by [54] (see also paper [80]) and for non-flat accretion flows by [79]. A possibility to observe mirages (shadows) around black holes using space based interferometers (like Radioastron space radio telescope) was discussed in paper [81].…”
Section: Discussionmentioning
confidence: 99%
“…We used an approach discussed in detail in papers [38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. The approach was used in particular to simulate spectral line shapes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several observations show that there are various scenarios where the magnetic fields and general relativity can not be neglected . One of them is the presence of strong magnetic fields in active galactic nuclei [6,7,8,9]. These nuclei are known to produce more radiation than the rest of the entire galaxy and directly affect its structure and evolution.…”
Section: Introductionmentioning
confidence: 99%